Ethical problems experienced in a supervised curricular internship in nursing in an integrated curriculum - Burgatti, Juliane Cristina; Bracialli, Luzmarina Aparecida Doretto; Oliveira, Maria Amelia de Campos (Revista da Escola de Enfermagem da USP, 2013)
An exploratory, qualitative study with the objective of analyzing repercussions of the supervised curricular internship in the development of the ethical dimension of competency in undergraduate nursing students. Semistructured interviews were performed with 28 students, professors and nurse preceptors of a public institution of higher education in the state of São Paulo, during the period of October of 2010 to March of 2011. The empirical result was subjected to the technique of discourse analysis and resulted in the empirical categories: preservation of autonomy; social responsibility and respect in interpersonal relations in health care delivery and in the teaching – learning process; treatment and care from the ethical dimension; and, public responsibility and social justice. It was concluded that the phase that uses problematization as a method of teaching and learning provides critical reflection about professional practice in the services and system of health.